Serine protease PRSS55 is crucial for male mouse fertility via affecting sperm migration and sperm–egg binding - Shang, Xuan (Cell Mol Life Sci, 2018)
Testis-specific PRSS55 is a highly conserved chymotrypsin-like serine protease among mammalian species. So far, the physiological function of PRSS55 remains unknown. Here, we show that PRSS55 is a GPI-anchored membrane protein, specifically expressed in adult mouse testis and mainly observed in the luminal side of seminiferous tubules and sperm acrosome. Mice deficient for Prss55 develop male infertile with normal reproduction-related parameters observed. Interestingly, in vivo fertilization rate of Prss55(−/−) males is dramatically decreased, possibly due to incapable migration of Prss55(−/−) sperm from uterus into oviduct. However, in vitro fertilization rate has no difference between two genotypes although Prss55(−/−) sperm presents defective recognition/binding to zona-intact or zona-free oocytes. Further study reveals that mature ADAM3 is almost undetectable in Prss55(−/−) sperm, while precursor ADAM3 remains unchanged in the testis. However, it is shown that ADAM3 has no interaction with PRSS55 by immunoprecipitation with anti-PRSS55 antibody. The expression levels of several proteins known to be related to the observed phenotypes remain comparable between wt and Prss55(−/−) mice. Moreover, we found that Prss55 deficiency has no effect on PRSS37 or vice versa albeit two mutant males share almost the same phenotypes. Microarray analysis reveals a total of 72 differentially expressed genes in Prss55(−/−) testis, most of which are associated with cellular membrane and organelle organization, protein transport and complex assembly, and response to stimulus and signaling. In conclusion, we have demonstrated that PRSS55 plays vital roles in regulating male fertility of mice, including in vivo sperm migration and in vitro sperm–egg interaction, possibly by affecting the maturation of ADAM3 in sperm and the expression of multiple genes in testis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00018-018-2878-9) contains supplementary material, which is available to authorized users.